Seluang Fish (Rasbora sp.) Oil Improves Interleukin-17 Levels and Disease Activity in Rheumatoid Arthritis - Partan, Radiyati Umi; Mikhael, Rodry; Adinata, Triawan; Darma, Surya; Reagan, Muhammad; Kriswiastiny, Rina; Kusnadi, Yulianto; Salim, Eddy Mart (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Vitamin D has a role in downregulating the proinflammatory cytokines as well as promoting the antiinflammatory pathway in rheumatoid arthritis (RA). Seluang fish (Rasbora sp.) has potency as a new source of vitamin D. Previous study had proven Seluang fish oil efficacy in systemic lupus erythematosus. However, there are no trials that prove its efficacy in RA yet. Hence, this study was conducted to find out the ability of Seluang fish oil to improve proinflammatory cytokines, vitamin D levels, and disease activity in RA.METHODS: A clinical trial with a randomized and double-blind method was done in two groups, each one consisting of 17 RA subjects. One group was given 500 mL of a Seluang fish oil capsule (contains 665 IU cholecalciferol), while the other group was given a placebo daily, for 12 consecutive weeks. Measurements of the RA disease activity score 28 erythrocyte sedimentation rate (DAS28-ESR) and DAS28 C-reactive protein (DAS28-CRP), as well as measurement of interleukin (IL)-6, IL-17, and vitamin D levels by using immunoassay method were performed before and after the supplementation.RESULTS: Significant alterations in the lower levels of IL-17 were observed in the Seluang fish oil group (p=0.031), but not in the placebo group (p=0.320). Reduction of DAS28-ESR (p=0.000) and DAS28-CRP (p=0.000) score demonstrated that the Seluang fish oil supplementation was useful in reducing RA disease activity. No significant shift was observed in either vitamin D (p=0.967) or IL-6 levels (p=0.076) after Seluang Fish Oil supplementation.CONCLUSION: Seluang fish oil is effective in lowering IL-17 levels, DAS28-ESR, and DAS28-CRP, but not in improving vitamin D level or lowering IL-6 level in RA patients.KEYWORDS: rheumatoid arthritis, seluang fish oil, interleukin-6, interleukin-17, vitamin D, DAS28